2021
DOI: 10.1007/s40588-021-00161-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effectiveness of Pre-harvest Meat Safety Interventions to Control Foodborne Pathogens in Broilers: a Systematic Review

Abstract: Purpose of Review Ensuring broilers’ meat safety is a priority to policy makers, producers, and consumers. This systematic review aims to update the recent knowledge on pre-harvest interventions to control main foodborne pathogens in broilers and to assess their effectiveness. Recent Findings A total of 815 studies were retrieved from PubMed® and Web of Science for 13 pathogens. In total, 51 studies regarding Campylobacter spp., Salmonella spp., VTEC, ESBL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Such work was framed in the context of the RIBMINS Cost Action (please refer to the Acknowledgements section). Likewise, the methods followed are similar to those described by Pessoa et al [4] and the work presented here was conducted by the same two review coordinators, and two volunteer researchers. The backbone of the methodology used followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement [5] and EFSA's guidelines for conducting systematic reviews for food and feed safety assessments [6].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such work was framed in the context of the RIBMINS Cost Action (please refer to the Acknowledgements section). Likewise, the methods followed are similar to those described by Pessoa et al [4] and the work presented here was conducted by the same two review coordinators, and two volunteer researchers. The backbone of the methodology used followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement [5] and EFSA's guidelines for conducting systematic reviews for food and feed safety assessments [6].…”
Section: Methodsmentioning
confidence: 99%
“…The trials are repeated across different categories if they fit in more than one type of intervention. 4 Examples of other interventions tested are off-site early weaning, washing and disinfecting of lorries, split marketing approaches, and different space allowances. * Trials which reported at least one positive result (i.e., reduction of Salmonella shedding, increase of protective immunity).…”
Section: Salmonellamentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the host and pathogen, controlling for water and feed contamination may nevertheless achieve contrasting results. In a recent systematic review, Pessoa et al [99] demonstrated that biosecurity measures including those targeting water and feed contaminations might be inefficient in the case of Salmonella in chickens. In line with this, water disinfection and feed hygiene may also only slightly affect the epidemiology of E. coli O157:H7 in cattle [97].…”
Section: Husbandry Practicesmentioning
confidence: 99%